Innovative Practices: Integration of Deep Learning and Values Education, Realizing 8 Dimensions of Graduate Profile - Kembara, Maulia Depriya (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Independent Curriculum encourages learning transformation that focuses on character development and 21st-century competencies through the integration of deep learning, value education, and eight dimensions of the Graduate Profile. This article aims to describe the results of community service in the form of a workshop for 60 high school Biology teachers in Cirebon Regency, which aims to improve teachers' understanding and skills in designing integrative learning. The method used is participatory-based training, equipped with pre-post assessment, simulation of lesson plan preparation, and assessment of Teaching Program Plan (RPP) products with standardized rubrics. The results of the analysis showed a significant increase in understanding the concept and application of character values ​​in the RPP. Most teachers use a project-based learning approach, ethical discussions, and problem-solving that support the strengthening of the graduate profile dimension. The main obstacles found were limited facilities and time, although they did not significantly reduce the quality of innovation. This activity shows that integrative workshops play an important role in building teacher pedagogical competence and realizing meaningful, contextual, and value-oriented Biology learning.